Greywater Treatment using Integrated Sand Filtration with Ultrafiltration for Reuse - El-Wattar, Aya (AUC Knowledge Fountain, 2023)
Membrane flux was observed and the two membrane sizes that achieved stable flux were chosen to be used in the later stages of the study. The chosen membranes were of 300 kDa and 400 kDa Molecular Weight Cutoff (MWCO). The third phase of the study involved running the full system on synthetic greywater then on real greywater. The parameters investigated were COD, TSS, Turbidity and BOD5. Total COD removal after sand filtration, 300kDa UF and 400 kDa UF was 65, 66 and 73.4% respectively. Total TSS removal after sand filtration, 300kDa UF and 400 kDa UF was 93.1, 98 and 98.1% respectively. Total turbidity removal after sand filtration, 300kDa UF and 400 kDa UF was 82.1, 85.8 and 83.8% respectively. And total BOD5 removal after sand filtration, 300kDa UF and 400 kDa UF was 59.1, 90.8 and 96.5% respectively. Overall, the system showed resilience to TSS shock loads, and all effluents from sand filter and ultrafiltration membranes complied with the Egyptian Code of Wastewater Reuse Category A (TSS less than or equal 15 mg/l). Membrane effluents BOD5 concentrations also complied with the limits for Category A in the Egyptian code (BOD5 less than or equal 15 mg/l). All membrane effluents satisfied category A limit in the Egyptian Code for Wastewater Reuse in Agriculture for BOD5 ( 15 mg/l).